2016
DOI: 10.1021/acs.jpcb.6b06135
|View full text |Cite
|
Sign up to set email alerts
|

Selective Electrochemical versus Chemical Oxidation of Bulky Phenol

Abstract: The electrochemical oxidation of selected tert-butylated phenols 2,6-di-tert-butyl-4-methylphenol (1), 2,6-di-tert-butylphenol (2), 2,4,6-tri-tert-butylphenol (3), 2-tert-butylphenol (4), and 4-tert-butylphenol (5) was studied in an aprotic environment using cyclic voltammetry, square-wave voltammetry, and UV-vis spectroscopy. All compounds exhibited irreversible oxidation of the corresponding phenol or phenolate ion. Compound 2 was selectively electrochemically oxidized, while other phenol analogues underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…These values exceed the reported literature data [11] in acetonitrile solution by about 0.3 V. The anion [ MeO t Bu2 PhO] − has the most negative redox potential of the here prepared phenolates and reaches that of zinc, which qualifies the anion as an organic zinc mimic [19] . In contrast to the reversible redox reaction of the sterically encumbered phenolates [ MeO t Bu2 PhO] − and [ t Bu3 PhO] − , the [PhO] − anion shows an irreversible oxidation at E Ox =−0.12(1) V vs. SCE due to a facile recombination of the formed radicals [20] . The anions [C 10 H 7 O] − and [ Me t Bu2 PhO] − are irreversibly oxidized as well.…”
Section: Resultsmentioning
confidence: 98%
“…These values exceed the reported literature data [11] in acetonitrile solution by about 0.3 V. The anion [ MeO t Bu2 PhO] − has the most negative redox potential of the here prepared phenolates and reaches that of zinc, which qualifies the anion as an organic zinc mimic [19] . In contrast to the reversible redox reaction of the sterically encumbered phenolates [ MeO t Bu2 PhO] − and [ t Bu3 PhO] − , the [PhO] − anion shows an irreversible oxidation at E Ox =−0.12(1) V vs. SCE due to a facile recombination of the formed radicals [20] . The anions [C 10 H 7 O] − and [ Me t Bu2 PhO] − are irreversibly oxidized as well.…”
Section: Resultsmentioning
confidence: 98%
“…This is approximately 0.5 V lower compared to the oxidation potential of tri‐substituted phenols such as 2,4,6‐tri‐ tert ‐butylphenol or 2,4,6‐trimethylphenol that oxidize at ca. 1.0 V (vs. Fc/Fc + ), [58, 59] which reflects the anionic state of the phenolic oxygen atom in K‐Im Ph2 NNO t Bu . A reduction event, C ( E p,c = −1.66 V), is observed that only occurs after A has taken place (see Figure S71), prompting us to assign it to the electrochemical reduction of the phenoxyl radical.…”
Section: Resultsmentioning
confidence: 99%
“…2V) and the relatively diffuse nature of both signals reflects the highly irreversible nature of this redoxc ouple and is consistent with previous observations made for the electrochemical behaviouro fs ubstituted phenolsi nc oordinatings olvents. [58,59] Moreover,t he structure of the ligand salt in solution is likely very dynamic, involving imidazole lability,s olvent coordination to the potassium iona nd possible coordination equilibria between monomeric and dimeric states, all of which contribute to the diffuse and irreversible nature of the electrochemical events. The electrochemical responses B and D (that occur at approximately À0.75 V) are very minor and becomel ess well defined at highers can rates (Figure S70).…”
Section: Electrochemistrymentioning
confidence: 99%
“…Thus, it is important to develop an adhesive-like material to remove the organic pollutants from water bodies to minimize pollution [11][12][13]. Many techniques have been used to remove phenol from wastewater such as photocatalytic degradation, membrane filtration, chemical oxidation, and solvent extraction [14][15][16][17][18][19][20][21]. Recently, Wang et al prepared 2D/2D γ-MnO 2 /rGO using rGO and KMnO 4 for the catalytic ozonation of 4-chlorophenol in the presence of PMS [22].…”
Section: Introductionmentioning
confidence: 99%